1981
DOI: 10.1083/jcb.88.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Serum-free growth of normal and transformed fibroblasts in milk: differential requirements for fibronectin.

Abstract: Bovine milk may be used as a supplement for the serum-free growth of certain fibroblastic cells in culture. The growth properties of three representative cell types in milksupplemented medium were examined ; fibroblastic cell strains, fibroblastic cell lines, and transformed fibroblasts . Transformed fibroblasts, which included RNA and DNA tumor virustransformed cells and carcinogen-transformed cells, grew in milk . Instead of growing attached to the culture dishes, as they normally do in serum, transformed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Fibroblasts are a cell type that is representative of the skin and have been widely studied. [43][44][45] It was therefore decided to investigate them further, by comparing the activating effects of mare's colostrum and milk on fibroblast proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts are a cell type that is representative of the skin and have been widely studied. [43][44][45] It was therefore decided to investigate them further, by comparing the activating effects of mare's colostrum and milk on fibroblast proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementation of cell culture media with milk, colostrum and whey extracts has been reported to improve the growth rate of many cell types, mostly epithelial cells from kidney and skin, but also fibroblasts, smooth muscle cells and chondrocytes from cartilage (Klagsbrun, 1980;Sereni & Baserga, 1981;Steimer & Klagsbrun, 1981;Belford et al, 1995;Francis, Regester, Webb, & Ballard, 1995). The activity of milk to promote cell growth has been related to many of its constituents, including nutrients such as minerals and vitamins (Alais, 1984) and amino acids such as glutamine (Rombeau, 1990), hormones (Nabet, Belleville-Nabet, & Linden, 1991) and growth factors including HMGF (Human Growth Factor)-I, -II and -III (Shing & Klagsbrun, 1984), IGF (Insulinlike Growth Factor) (Campbell & Baumrucker, 1989), TGF (Tumour Growth Factor) (Cox & Burk, 1991) and FGF (Fibroblast Growth Factor) .…”
Section: Introductionmentioning
confidence: 99%
“…Propagation of non-hybridoma cell lines in colostrum or milk supplemented media has also been attempted by other workers (Klagsbrun, 1980;Steimer and Klagsbrun, 1981). Inhibition by colostrum was reported to be cell line de pende nt.…”
Section: Croissance (A) Et Production D'anticorps (B) Des Cellules D'mentioning
confidence: 97%
“…Colostrum did not support human and rat fibroblasts in long-term culture, whereas canine kidney epithelial cell (MOCK) grew exponentially (Klagsbrun, 1980). Steimer and Klagsbrun (1981) suggested that milk was deficient in attachment factor su ch as fibronectin. This may not be the only reason for inhibition of VI0103 hybridoma by colostrum since coating of 24-well plate with collagen did not improve binding and multiplication of hybridoma.…”
Section: Croissance (A) Et Production D'anticorps (B) Des Cellules D'mentioning
confidence: 99%